How relevant are capital flows for house prices in emerging economies? - Marco Hernández Vega (Banco de México, 2019)
This work studies the impact of Foreign Direct Investment (FDI) and portfolio flows on house prices of emerging market economies using a static factors panel VARX model. The results show that an increase in both FDI and portfolio flows leads to higher house prices, but that portfolio flows have a more persistent effect. This work also finds that mortgage credit, as proxy of housing demand, is an important variable in house price dynamics in the sense that it has a higher positive impact on house prices than any of the other endogenous variables included. The results are robust to different specifications of the model, such as adding additional lags or changing the order in which the endogenous variables enter the model.
Keywords: C32; E44; F32; G21; 330; Emerging Markets; Capital Flows; House Prices